Tracing Orpheus: studies of Orphic fragments : in honour of Alberto Bernabé - Santamaría Álvarez, Marco Antonio; Herrero de Jáuregui, Miguel; Luján, Eugenio R.; Torallas Tovar, Sofía; Martín Hernández, Raquel; Jiménez San Cristóbal, Ana Isabel; Bernabé Pajares, Alberto (Sozomena, 2012)
This volume sheds light on the most relevant pieces of evidence for ancient Orphism, collected in the recent edition by Alberto Bernabé. It contains 65 short new studies on Orphic fragments by leading international scholars who comment one of the most controversial phenomena in Antiquity from a plurality of perspectives. Readers will acquire a global vision of the multiple dimensions of the Orphic tradition, as well as many new insights into particular Orphic fragments